Payment methods for healthcare providers working in outpatient healthcare settings - Jia, Liying; Meng, Qingyue; Scott, Anthony; Yuan, Beibei; Zhang, Lu (Cochrane database of systematic reviews, 2021)
Changes to the method of payment for healthcare providers, including pay-for-performance schemes, are increasingly being used by governments, health insurers, and employers to help align financial incentives with health system goals. In this review we focused on changes to the method and level of payment for all types of healthcare providers in outpatient healthcare settings. Outpatient healthcare settings, broadly defined as 'out of hospital' care including primary care, are important for health systems in reducing the use of more expensive hospital services. To assess the impact of different payment methods for healthcare providers working in outpatient healthcare settings on the quantity and quality of health service provision, patient outcomes, healthcare provider outcomes, cost of service provision, and adverse effects. We searched CENTRAL, MEDLINE, Embase (searched 5 March 2019), and several other databases. In addition, we searched clinical trials platforms, grey literature, screened reference lists of included studies, did a cited reference search for included studies, and contacted study authors to identify additional studies. We screened records from an updated search in August 2020, with any potentially relevant studies categorised as awaiting classification. Randomised trials, non-randomised trials, controlled before-after studies, interrupted time series, and repeated measures studies that compared different payment methods for healthcare providers working in outpatient care settings. We used standard methodological procedures expected by Cochrane. We conducted a structured synthesis. We first categorised the payment methods comparisons and outcomes, and then described the effects of different types of payment methods on different outcome categories. Where feasible, we used meta-analysis to synthesise the effects of payment interventions under the same category. Where it was not possible to perform meta-analysis, we have reported means/medians and full ranges of the available point estimates. We have reported the risk ratio (RR) for dichotomous outcomes and the relative difference (as per cent change or mean difference (MD)) for continuous outcomes. We included 27 studies in the review: 12 randomised trials, 13 controlled before-and-after studies, one interrupted time series, and one repeated measure study. Most healthcare providers were primary care physicians. Most of the payment methods were implemented by health insurance schemes in high-income countries, with only one study from a low- or middle-income country. The included studies were categorised into four groups based on comparisons of different payment methods. (1) Pay for performance (P4P) plus existing payment methods compared with existing payment methods for healthcare providers working in outpatient healthcare settings P4P incentives probably improve child immunisation status (RR 1.27, 95% confidence interval (CI) 1.19 to 1.36; 3760 patients; moderate-certainty evidence) and may slightly increase the number of patients who are asked more detailed questions on their disease by their pharmacist (MD 1.24, 95% CI 0.93 to 1.54; 454 patients; low-certainty evidence). P4P may slightly improve primary care physicians' prescribing of guideline-recommended antihypertensive medicines compared with an existing payment method (RR 1.07, 95% CI 1.02 to 1.12; 362 patients; low-certainty evidence). We are uncertain about the effects of extra P4P incentives on mean blood pressure reduction for patients and costs for providing services compared with an existing payment method (very low-certainty evidence). Outcomes related to workload or other health professional outcomes were not reported in the included studies. One randomised trial found that compared to the control group, the performance of incentivised professionals was not sustained after the P4P intervention had ended. (2) Fee for service (FFS) compared with existing payment methods for healthcare providers working in outpatient healthcare settings We are uncertain about the effect of FFS on the quantity of health services delivered (outpatient visits and hospitalisations), patient health outcomes, and total drugs cost compared to an existing payment method due to very low-certainty evidence. The quality of service provision and health professional outcomes were not reported in the included studies. One randomised trial reported that physicians paid via FFS may see more well patients than salaried physicians (low-certainty evidence), possibly implying that more unnecessary services were delivered through FFS. (3) FFS mixed with existing payment methods compared with existing payment methods for healthcare providers working in outpatient healthcare settings FFS mixed payment method may increase the quantity of health services provided compared with an existing payment method (RR 1.37, 95% CI 1.07 to 1.76; low-certainty evidence). We are uncertain about the effect of FFS mixed payment on quality of services provided, patient health outcomes, and health professional outcomes compared with an existing payment method due to very low-certainty evidence. Cost outcomes and adverse effects were not reported in the included studies. (4) Enhanced FFS compared with FFS for healthcare providers working in outpatient healthcare settings Enhanced FFS (higher FFS payment) probably increases child immunisation rates (RR 1.25, 95% CI 1.06 to 1.48; moderate-certainty evidence). We are uncertain whether higher FFS payment results in more primary care visits and about the effect of enhanced FFS on the net expenditure per year on covered children with regular FFS (very low-certainty evidence). Quality of service provision, patient outcomes, health professional outcomes, and adverse effects were not reported in the included studies. For healthcare providers working in outpatient healthcare settings, P4P or an increase in FFS payment level probably increases the quantity of health service provision (moderate-certainty evidence), and P4P may slightly improve the quality of service provision for targeted conditions (low-certainty evidence). The effects of changes in payment methods on health outcomes is uncertain due to very low-certainty evidence. Information to explore the influence of specific payment method design features, such as the size of incentives and type of performance measures, was insufficient. Furthermore, due to limited and very low-certainty evidence, it is uncertain if changing payment models without including additional funding for professionals would have similar effects. There is a need for further well-conducted research on payment methods for healthcare providers working in outpatient healthcare settings in low- and middle-income countries; more studies comparing the impacts of different designs of the same payment method; and studies that consider the unintended consequences of payment interventions.